2015
DOI: 10.13004/kjnt.2015.11.2.63
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factor Analysis for the Recurrence of Chronic Subdural Hematoma: A Review of 368 Consecutive Surgical Cases

Abstract: IntroductionA chronic subdural hematoma (CSDH) is a well-known disease of intracranial hemorrhage in old people. The burr hole trephination is the usual treatment of CSDH with a good outcome and prognosis.Despite the simple treatment of CSDH, the recurrence rate of CSDH is not low. The recurrence rate of CSDH ranged between 10% and 33% in previous studies.26) Many studies have been reported on factors associated with the recurrence of CSDH; however, the results were inconsistent. The purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 27 publications
2
23
2
Order By: Relevance
“…If large or symptomatic, it is addressed surgically through burr hole trephination or craniotomy, with a reported recurrence rate ranging from 2.3% to 38.7% for different surgical techniques. 6,7,10,20,21 Although many investigators have tried to elucidate factors responsible for recurrence and reoperation, there is an ongoing debate about which parameters are relevant in this matter. Among the established factors are presence of coagulopathy or anticoagulant drug use, presence of CSDH loculations, larger preoperative hematoma volume, presence of significant postoperative residual hematoma, and postoperative pneumocephalus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If large or symptomatic, it is addressed surgically through burr hole trephination or craniotomy, with a reported recurrence rate ranging from 2.3% to 38.7% for different surgical techniques. 6,7,10,20,21 Although many investigators have tried to elucidate factors responsible for recurrence and reoperation, there is an ongoing debate about which parameters are relevant in this matter. Among the established factors are presence of coagulopathy or anticoagulant drug use, presence of CSDH loculations, larger preoperative hematoma volume, presence of significant postoperative residual hematoma, and postoperative pneumocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Among the established factors are presence of coagulopathy or anticoagulant drug use, presence of CSDH loculations, larger preoperative hematoma volume, presence of significant postoperative residual hematoma, and postoperative pneumocephalus. 3,6,7,10,13,16,20,[23][24][25] In 2 meta-analyses that included 19 randomized clinical trials and 250 studies each, heterogeneity of hematoma on CT, use of intraoperative irrigation, and drain use were identified as factors predictive of the need for reoperation. 2,14 with respect to a few factors, likely missing the interaction between other variables and confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Over numerous studies, the recurrence rate of this disorder is reported to be 9%–33%[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 ] and these studies also analyzed the risk factors for postoperative recurrence. The reported risk factors are laterality of hematomas being bilateral,[ 1 5 16 17 21 22 ] preoperative hematoma width and midline shift being greater,[ 5 10 11 16 18 19 23 ] volume of postoperative residual air and subdural space being greater,[ 2 4 8 13 14 18 19 20 ] preoperative hematoma densities,[ 2 4 6 7 11 13 17 18 19 ] medical history including diabetes mellitus, hypertension, leukemia, liver disease, chronic renal failure and seizure,[ 5 7 17 23 ] and intake of anticoagulant or thrombolytic drugs. [ 7 15 ] However, the findings were not consistent between the studies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Although a relatively simple surgical treatment usually consisting of burr hole opening and drainage of the hematoma is effective, recurrence occurs postoperatively at 5.4-18.1%. [5][6][7][8][9][10][11][12][13][14][15][16] In symptomatic reaccumulation of hematoma, repetitive drainage or craniotomy is often required, but redo surgery may have a negative impact on the neurological status and patients' quality of life. Several retrospective analyses have reported the benefit of adjuvant medical treatment, such as corticosteroid, 17,18) atorvastatin, 19,20) tranexamic acid, 21) etizolam, 22) and angiotensin-converting enzyme (ACE) inhibitor, 23) to lower the recurrence rate.…”
Section: Introductionmentioning
confidence: 99%